Temperature-Driven Biodiversity Change: Disentangling Space and Time. (19th September 2018) - Waldock, Conor; Dornelas, Maria; Bates, Amanda E
Abstract: Temperature regimes have multiple spatial and temporal dimensions that have different impacts on biodiversity. Signatures of warming across these dimensions may contribute uniquely to the large-scale species redistributions and abundance changes that underpin community dynamics. A comprehensive review of the literature reveals that 86% of studies were focused on community responses to temperature aggregated over spatial or temporal dimensions (e.g., mean, median, or extremes). Therefore, the effects of temperature variation in space and time on biodiversity remain generally unquantified. In the present article, we argue that this focus on aggregated temperature measures may limit advancing our understanding of how communities are being altered by climate change. In light of this, we map the cause-and-effect pathways between the different dimensions of temperature change and communities in space and time. A broadened focus, shifted toward a multidimensional perspective of temperature, will allow better interpretation and prediction of biodiversity change and more robust management and conservation strategies.